Integrated restoration of forested ecosystems to achieve multiresource benefits : proceedings of the 2007 National Silviculture Workshop - National Silviculture Workshop (2007 : Ketchikan, Alaska); Deal, Robert L. (Robert Leslie); United States. Forest Service. ([Portland, OR] : United States Dept. of Agriculture, Forest Service, Pacific Northwest Research Station, 2008)
"January 2008." Workshop sponsored by the U.S. Department of Agriculture Forest Service and held May 7-10, 2007 in Ketchikan, Alaska. Includes bibliographical references. Mode of access: Internet.